Correlation between serum bilirubin and serum ferritin Level in thalassaemia patients (Bangladesh Journal of Medical Biochemistry, 2013)
Thalassaemia is the most common hereditary disorder in the world including Bangladesh. Beta thalassaemia major and Hb-E thalassaemia both are common in our country. Iron overload causes most of the mortality and morbidity associate with thalassaemia. To assess the iron over load and liver function a cross sectional comparative study was carried out in the Department of Biochemistry, Dhaka Medical College, Dhaka in collaboration with Thalassaemia Center and Department of Pathology, Dhaka Shishu Hospital, Dhaka during the period of July 2006 to June 2007. The study was carried out with the patients who visited regularly in Dhaka Shishu Hospital Thalassaemia Centre (DSHTC) and had multiple transfusions (more than five) and age more than 2 years. To compare the state of liver function with normal healthy individuals' normal healthy persons were also included. Total 70 subjects were included in this study. The study subjects were distributed into two groups, the group - A (cases, n=40) and group - B (healthy controls, n=30). According to the major types of thalassaemia present in our country, group -A again divided into two, group - AI ?-thalassaemia major (n=12) and group - AII of Hemoglobin E ?-thalassaemia (n=28). The mean of serum Bilirubin in group - A and group - B were (2.04 ±0.70) mg/dl and (0.67±0.15) mg/dl respectively. Group - A had higher serum bilirubin than group -B in p value